Effects of Anxiety Symptoms on Undergraduate Students' Quality of Life: Mediating Role of Perceived Social Support and Self-esteem - Tran, Le-Thanh; Le, Duy-Hung; Pham, Quang Dao (Psychology Hub, 2024)
This paper was conducted to examine the mediating role of perceived social support and self-esteem in the relationship between symptoms of anxiety and quality of life. A cross-sectional survey of 308 undergraduate students was conducted. The results show that anxiety symptoms have a negative effect on the student's quality of life. In addition, perceived social support and self-esteem play a partial mediating role in the relationship between anxiety symptoms and quality of life. Our findings help to better understand the mechanism that affects the quality of life of undergraduate students. This is also the basis for the implementation of improving the quality of life and reducing the impact of anxiety on the quality of life of undergraduate students.